Faktor-Faktor yang Mempengaruhi Siswa SMK Melanjutkan ke Perguruan Tinggi dalam Perspektif Akademik, Ekonomi, dan Sosial - Putri, Uriyani Eka; Estriyanto, Yuyun; Sukatiman, Sukatiman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study was to determine the effect, of economic, academic, and social environment on the career choices of vocational students after graduating from vocational high school. The method used in this research is the postmodern phenomenology model. The location of research was conducted at SMK Negeri 9 Surakarta. Data collection techniques in research use several methods and are adapted to the circumstances and data needs needed in research. The data collection method consisted of observation, interviews, and document analysis. The process of obtaining data in research goes through the following stages: (1) the orientation or description stage; (2) the reduction or focus stage; (3) the selection stage. The result of this research is that the economic factor comes from the income of parents and the income of vocational students. Academic achievement factors come from the interests, talents, and personal motivation of students and parents. Social factors come from the family and community environment.